A Study on the Inhibitory Effect of Matrine on Gastric Cancer SGC-7901 Cells - Song, Shimao (African Networks on Ethnomedicines, 2013)
The objective of this paper was to investigate the antitumour mechanism of action of matrine by studying its inhibitory effect on gastric cancer SGC-7901 cells. SGC-7901 cells were chosen, and cell-killing capacity of matrine on gastric cancer SGC-7901 cells was determined using MTT assay and single PI staining assay. The results showed that matrine had an inhibitory effect on gastric cancer SGC-7901 cells, which was somewhat dose-dependent. The study concluded that matrine has a significant in-vitro inhibitory effect on SGC-7901 tumour cells, influences cell cycle of SGC-7901 cells, and induces their apoptosis.